Soil Cover of the Kuybyshev Reservoir Islands near the Settlement of Zaymishche - V.I. Kulagina (Učënye Zapiski Kazanskogo Universiteta. Seriâ Estestvennye Nauki, 2016)
The history of formation of the Kuybyshev Reservoir islands near the settlement of Zaymishche has been considered. The soil cover structure of the islands has been described. The genesis and physical-chemical properties of the soils of the islands have been investigated. It has been shown that most of the studied soils, which belonged to the group of alluvial soddy soils before the creation of the reservoir, are characterized by the light granulometric composition, small thickness of the humus horizon, and low humus content. The statistical analysis has shown that flooding by the reservoir waters did not have any significant impact on the content of humus and nitrogen in the soils, but influenced the distribution of values of soil acidity, exchangeable bases, capacities of cationic exchange, and hydrolytic acidity.